THE IMPACT OF TRANSLANGUAGING APPROACH ON TEACHING ARABIC READING IN A MULTILINGUAL CLASSROOM - Bin-Tahir, Saidna Zulfiqar; Saidah, Ummu; Mufidah, Nuril; Bugis, Riki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Â The study aimed at measuring the effect of translanguaging approach in teaching Arabic reading comprehension to the second semester students of Indonesian Education Department, Universitas Iqra Buru. 64 students involved as the participants through simple random sampling technique. 32 students participated in each of the experimental and control group. The researchers used reading test of written test to obtain information about the studentsâ€™ achievemnt in reading on the use of translanguaging approach and it was distributed to the respondents after the last treatment given. To find out the mean score, standard deviation and the t-test value between the pretest and the posttest the researchers used the SPSS 17 program. The researchers found that the use of translanguaging approach in learning Arabic reading comprehension improves the studentsâ€™ ability of Arabic reading comprehension is better than the conventional method.